Importance of Ship Tours in Development Strategy of Croatian Tourism - Christian Stipanović; Danijela Gračan (Zbornik Radova Pravnog Fakulteta u Splitu, 2005)
Tourism reality is represented by new quality trends: changes in tourism behaviour, evolution and implementation of new forms of product, quality shifts in tourism management, ecology breakthrough and environment preservation. Seeking for a new adventures, tourists are turning to new sorts of services from which ship tours are outstanding. Tours represent the result of a tourist aspiration for travelling and expectation of getting acquainted with something new, it is a contrast to static vacation and mass tourism. It's price competitiveness stipulates a remarkable growth of travelling. Unfortunatelly, Croatia does not adequate valorize its natural resources base for implementation of ship tours and still haven't revived as a prestige cruising destination. It's growth (on ship cruising scene) comes out from enterprising špirit of some tour operators and is not the result of some conceived activity in development strategy of Croatian tourism.